Inventarisasi Tanaman Berkhasiat Obat di Desa Muara Baru Kecamatan Kota Kayu Agung Kabupaten Ogan Komering Ilir (OKI) - Otia, Rinny; Eddy, Syaiful; Kartika, Trimin (Universitas PGRI Palembang, 2024)
Research on Inventory of Medicinal Plants in Muara Baru Village, Kayuagung City District, Ogan Komering Ilir (OKI) Regency. The research uses a descriptive survey method and observation method. Based on the results of semi-structured interviews with the people of Muara Baru Village, Kota Kayuagung District, Ogan Komering Ilir (OKI) Regency, 19 types of plants were found that can be used to treat various diseases. Plant parts used as medicine include: leaves, rhizomes, seeds, roots, stems, fruit and flowers. including (63.15%), as many leaves as (26.32%), as many rhizomes as (21.05%), as many flowers as (15.79%), as many roots as (10.53%), as many stems as (10 .53%), and seeds as much as (5.26%). Ways of processing plants as traditional medicine by the people of Muara Baru Village, Kota Kayu Agung District, Ogan Komering Ilir (OKI) Regency include boiling, kneading, blending, consuming directly and the methods of use are drinking, eating, rubbing on and using straight away.